Great power governmentality? Coincidence and parallelism in the new strategic guidance for the US Department of Defense. (December 2014) - Vasilache, Andreas
In January 2012, the US administration released new strategic guidance for the Department of Defense entitled 'Sustaining US Global Leadership: Priorities for 21st Century Defense'. Two different security approaches seem to coincide in this document. By providing a governmental reading of the new strategic guidance, the aim of this article is to discuss if and how the guidance links a sovereign security understanding of great power politics on one side to governmental rationalities on the other. First, the guidance is discussed with regard to its main aims and strategies; then, second, the impact of governmentality in the guidance is revealed and systematized. Finally, the function that governmental logics have in the document, and the conceptual and political role that the minimally mediated encounter of sovereign (military) power politics with governmental rationalities plays, are considered.